COMPARISON OF O. SLASTION'S SCHOOL BUILDING DECORATION WITH NATIONAL STYLE SEARCHES IN SCHOOL ARCHITECTURE OF OTHER COUNTRIES AT THE TURN OF THE XX CENTURY - ВЕРЕС, М. К. (Art and Design, 2022)
Purpose – to identify and compare the elements of decoration of school buildings in Ukraine designed by O. Slastion with national and stylistic searches in the school architecture of other countries built at the turn of the XX century. Methodology. The research is based on the literary-analytical review of scientific works concerning the researched objects of school buildings according to the projects of the architect O. Slastyon which have been preserved on the territory of Ukraine. The paper compares the decoration of facades with national-style searches in the school architecture of other countries on the example of schools in the United States and Canada built at the turn of the XX century. Results. At the beginning of the XX century, a law was passed on the introduction of compulsory primary education in Ukraine, part of which was territorially part of the Russian Empire at the time. To provide the population with educational institutions, the Ministry of Public Education allocated funds for the construction of schools for which the zemstvos were responsible. At the same time, school education is also being developed in other parts of the world, and numerous school buildings are being erected in rural areas of the more remote countries of the United States and Canada. It was found out that starting from 1909, first on the territory of Poltava Zemstvo, and later in other regions, according to the projects of architect O. Slastyon, numerous school buildings were built, which were often divided into one and two classrooms. The projects of these schools introduced theoretical provisions developed at the beginning of the century regarding the design and artistic decoration of folk schools in the style of Ukrainian Architectural Art Nouveau (in ukr. – UAM). In the projects of the provincial public schools of the USA and Canada, the most common type was one-class schools, which in most cases were built of wood. The study established the location and method of decorative elements on facades in comparison with national-style searches in school architecture of other countries on the example of provincial schools in the USA and Canada, which included such parts of the wall covering as: entrance group, decoration of towers and bell towers, decoration window openings, decoration of doors and cornices. Scientific novelty. The article identifies and analyzes the elements of decoration of the facades of folk rural schools in Ukraine built at the turn of the XX century in comparison with national-style searches in school architecture on the example of provincial schools in the USA and Canada. For the first time was considered the arrangement of decorative elements and was formed the typology of ornaments whitch were used by architect O. Slastyon on the facades of folk rural schools in Ukraine. Practical significance. The results of the study can be used as historical theoretical materials for the design of school buildings in the national style, as well as a factual basis, which is a continuation of the related topics to the study of domestic samples of historical decor of school buildings.